The effect of poly‐β‐hydroxybutyrate on the performance of Chinese mitten crab (Eriocheir sinensis Milne‐Edwards) zoea larvae. Issue 3 (21st November 2012) - Sui, Liying; Liu, Yu; Sun, Huixian; Wille, Mathieu; Bossier, Peter; De, Peter
Abstract Two experiments were conducted regarding the effect of poly‐β‐hydroxybutyrate (PHB) on the survival and development of Chinese mitten crab (Eriocheir sinensis Milne‐Edwards) larvae. Different PHB delivery approaches (particulate, enriched in filter feeding prey, or a combination of both) and feeding levels were applied to crab larvae from the zoea 2 (Z2) up to the megalopa stage. Bio‐encapsulation into rotifers and Artemia at a PHB dose of 100 mg L−1 seemed an efficient approach to deliver PHB to the larvae and resulted in a significantly enhanced survival, development rate and osmotic tolerance. The results indicate that PHB should only be applied as a feed additive rather than as a food source, and that the availability of an adequate amount of nutrients seems to be of major importance for the PHB to induce these beneficial effects.